2006
DOI: 10.1002/pssb.200671501
|View full text |Cite
|
Sign up to set email alerts
|

Formation of symmetric and asymmetric metal–semiconductor hybrid nanoparticles

Abstract: Multi-component nano-systems are created by combining two or more different materials yielding new chemical and physical properties. Here we report the selective anisotropic growth creating hybrid nanparticles of two different material systems, a metal onto a semiconductor. We developed a simple method for the selective growth of gold tips onto the apexes of colloidal semiconductor nanorods and tetrapods. This combination provides new functionalities to the nanostructures, the most important of which is the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 15 publications
0
20
0
Order By: Relevance
“…6,7 These structures underwent a change from two-sided (dumbbells) to one-sided (matchstick) *soennichsen@uni-mainz.de Tel: +49 (0) 6131 39 24313 Fax: +49 (0) 6131 39 26747 growth attributed to intra-particle electrochemical Ostwald-ripening where the smaller metal domains are dissolved in favor of the larger tip. 25,26 The gold tips on the semiconductor rods can both serve as anchoring points for self-assembly 6,27,28 and accumulate electrons photogenerated in the semiconductor to drive redox reactions. 21,23,29 Until now, it has not been possible to control the metal size in those systems.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 These structures underwent a change from two-sided (dumbbells) to one-sided (matchstick) *soennichsen@uni-mainz.de Tel: +49 (0) 6131 39 24313 Fax: +49 (0) 6131 39 26747 growth attributed to intra-particle electrochemical Ostwald-ripening where the smaller metal domains are dissolved in favor of the larger tip. 25,26 The gold tips on the semiconductor rods can both serve as anchoring points for self-assembly 6,27,28 and accumulate electrons photogenerated in the semiconductor to drive redox reactions. 21,23,29 Until now, it has not been possible to control the metal size in those systems.…”
Section: Introductionmentioning
confidence: 99%
“…Deposition of gold on a single side or on both sides of CdSe NCs was rst demonstrated by the reduction of gold(III) chloride at room temperature (rt) in a colloidal suspension of CdSe nanostructures (QDs, NRs and tetrapods) in toluene. [72][73][74] In this procedure, dodecylamine (DDA) acts both as the surfactant of the CdSe nanostructure and as the reducing agent, while didodecyldimethylammonium bromide (DDAB) is the surfactant for the gold in the organic medium.…”
Section: Colloidal Routes To Form M/sc Interfacesmentioning
confidence: 99%
“…The previously discussed, Au-tipped Cd-chalcogenide system provides further insight into the formation of asymmetric hybrid structures from symmetric ones. [72][73][74] Despite the symmetry of CdSe NRs in a colloidal solution, the gold complex is attracted to the tips. This stems from the combination of the following: (i) the tips are a location with a strong curvature, thus they have a high specic surface free energy (g), relative to the sides of the NRs, (ii) the surfactant passivation at the tip is less 'dense', with higher defect probability both due to geometric considerations and the different exposed crystal plains (which during the high-temperature growth of the wurtzite hexagonal CdSe phase of the NRs grow parallel to the c-axis, i.e., h001i).…”
Section: Colloidal Routes To Form M/sc Interfacesmentioning
confidence: 99%
“…211, 212 It was demonstrated that goldenized CdSe nanorods and tetrapods can be selfassembled into chains of rods via linking through the gold tips by adding hexane dithiol as a bifunctional ligand, which binds strongly and preferentially to the Au tips. 211 This technique can be used for directed self-assembly of multicomponent anisotropic semiconducting nanostructures for wiring them onto electrical circuitry.…”
Section: Other Potential Applicationsmentioning
confidence: 99%